National Judicial Reporting Program, 2002: (United States) ([Verlag nicht ermittelbar], 2005)
This data collection provides detailed information on the sentences and characteristics of convicted felons based on data collected from state courts. The 2002 survey was based on a sample of 300 counties selected to be nationally representative. The collection contains sociodemographic information such as age, race, and sex of the felon. Types of offenses committed include homicide, rape, and robbery. Data can be analyzed at the national level or by individual counties.